PESIAR DAN IJIN BERMALAM MENURUNKAN KECEMASAN MAHASISWA BARU AKPER KESDAM IV/DIPONEGORO: CRUISE AND NIGHT PERMISSION REDUCE ANXIETY OF NEW STUDENTS OF AKPER KESDAM IV/DIPONEGORO - Tuti Anggarawati; Novita Wulan Sari; Zara Bunganingrum; Lutfiana Dwi Arsih (JURNAL KEPERAWATAN SISTHANA, 2020)
The incidence of depression and anxiety that increases at the age of more than 15 years cannot be separated from the role and identity of students. Someone who has just entered the world of campus will be different from the condition of students who have been around for a long time with the world of campus. This condition is coupled with the position of students who have to live in dormitories where their friends in their environment do not match what they want and there are regulations that must be implemented as residents of the dormitory. Not a few students who experience social anxiety while undergoing college. The impact that arises due to anxiety is very influential on the lives of students. Cruise activities and overnight permits are intended to relieve temporary fatigue from the hectic academic activities by doing personal activities outside the dormitory. The purpose of this study was to determine the effect of cruises and overnight permits on reducing anxiety for new students. This research method is a quasi-experimental one group pre-test post-test design. The research sample uses total sampling. This study uses the DSS-21 instrument. The results showed that the highest level of anxiety during the pre-test was at the moderate level of anxiety as many as 19 children (29%), after the post-test showed the highest results at the normal level of anxiety as many as 28 children (43%), with a p-value is 0.000. The conclusion is that there is an effect of cruises and overnight permits on reducing anxiety in new students. The results of this study can be used for new students who experience anxiety due to facing new situations.